2016
DOI: 10.1021/acs.nanolett.6b02203
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Embedded Fabrication of Co2P Nanoparticles Encapsulated in N,P-Doped Graphene for Hydrogen Generation

Abstract: We developed a method to engineer well-distributed dicobalt phosphide (Co2P) nanoparticles encapsulated in N,P-doped graphene (Co2P@NPG) as electrocatalysts for hydrogen evolution reaction (HER). We fabricated such nanostructure by the absorption of initiator and functional monomers, including acrylamide and phytic acid on graphene oxides, followed by UV-initiated polymerization, then by adsorption of cobalt ions and finally calcination to form N,P-doped graphene structures. Our experimental results show signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(130 citation statements)
references
References 49 publications
3
125
0
Order By: Relevance
“…Regarding the durability problem, a number of recent studies showed that carbonencapsulation of nanoparticles (NPs) can considerably improve their long-term stability in harsh reaction conditions for electrochemical reactions. [24][25][26][27][28][29][30] For example, the Bao group reported that CoNi alloy NPs coated with graphene show good long-term durability (up to 1000 cycles). 31 Our IBS Center previously reported that encapsulation of FePt alloy NPs with carbon shell resulted in exceptional thermal stability at annealing temperature as high as 700 o C. 32 Being inspired by those examples, we conjectured that carbon shell formation can be a general strategy of providing physicochemical protection for various nanocatalysts, including metal phosphides, to achieve high stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Regarding the durability problem, a number of recent studies showed that carbonencapsulation of nanoparticles (NPs) can considerably improve their long-term stability in harsh reaction conditions for electrochemical reactions. [24][25][26][27][28][29][30] For example, the Bao group reported that CoNi alloy NPs coated with graphene show good long-term durability (up to 1000 cycles). 31 Our IBS Center previously reported that encapsulation of FePt alloy NPs with carbon shell resulted in exceptional thermal stability at annealing temperature as high as 700 o C. 32 Being inspired by those examples, we conjectured that carbon shell formation can be a general strategy of providing physicochemical protection for various nanocatalysts, including metal phosphides, to achieve high stability.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1,2] Water electrolysis is at heoretically attractivem ethod for the hydrogen evolution reaction( HER). [36] Significant effort has been made for the construction of Co 2 Pn anostructures and the regulation of its morphology and size for improving the HER performance. [3][4][5] Pt-basedc atalysts perform well in the HER; however, because of the high cost and lowa bundance of Pt metal on earth, variousn onprecious-metal-based electrocatalysts have been designed to tackle these problems.…”
Section: Introductionmentioning
confidence: 99%
“…60 No. 12 performed by E RHE =0.281+E SCE . Linear sweep voltammetry (LSV) was performed at a scan rate of 5 mV s −1 .…”
Section: Science China Materialsmentioning
confidence: 99%
“…Clean energy sources have attracted extensive attention from many researchers in the past few years, such as nuclear power [5,6], solar energy [7], wind energy [8], tidal power [9] and hydrogen [10,11]. Hydrogen, as a clean and sustainable energy carrier, is considered one of the most ideal candidates to replace fossil fuels in the future [3,12]. Efficient hydrogen production is critical for developing hydrogen energy technology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation